2018
DOI: 10.1002/mma.4809
|View full text |Cite
|
Sign up to set email alerts
|

Generalised magnetic polarizability tensors

Abstract: We present a new complete asymptotic expansion for the low-frequency time-harmonic magnetic field perturbation caused by the presence of a conducting (permeable) object as its size tends to zero for the eddy current regime of Maxwell's equations. The new asymptotic expansion allows the characterisation of the shape and material properties of such objects by a new class of generalised magnetic polarizability tensors, and we provide an explicit formula for their calculation. Our result will have important implic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 16 publications
3
52
0
Order By: Relevance
“…Still further, using (26), (24) becomes (22a), and in a similar manner, using (25), (27) becomes (22b) as desired. It also follows from (22a), and the linearity of the transmission problem (11)…”
Section: The Following Symmetric Bilinear Forms On Real Vectorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Still further, using (26), (24) becomes (22a), and in a similar manner, using (25), (27) becomes (22b) as desired. It also follows from (22a), and the linearity of the transmission problem (11)…”
Section: The Following Symmetric Bilinear Forms On Real Vectorsmentioning
confidence: 85%
“…9 We have extended the work of Ammari et al to provide a complete asymptotic expansion for the perturbed magnetic field, which allows an object to be characterised by generalised MPTs of which the rank 2 MPT is the simplest case. 11 In Ledger et al, 12 we have developed asymptotic expansions for the perturbed magnetic field that describe (a) the leading order term for a small inhomogeneous conducting permeable object and (b) the response in the case of multiple small conducting permeable objects, thus, extending the rank 2 MPT description of each of the objects to these cases. Some properties of the MPT are described in Ledger and Lionheart, 13 and the availability of the explicit formula for the isolated single object case has been communicated to the engineering community.…”
mentioning
confidence: 99%
“…A generalization of (11) has recently been derived [23], which extends the leading order term to a complete asymptotic expansion of the perturbed field. The higher order terms are expressed in terms of a new class of (higher rank) generalized MPTs (GMPTs) and higher order derivatives of G(x, z) and H 0 (z).…”
Section: Asymptotic Expansionmentioning
confidence: 99%
“…However, this is incorrect since, despite the substitution of the Taylor series expressions in (15), the integrands in R d (x) still depend on A , which itself is a function of α, and consequently, we cannot say that the remainder is of the form 4 with C independent of α. A different approach is required to achieve this rigorously, leading to the asymptotic expansion (11) [4], [23].…”
Section: A Validity Of (4)mentioning
confidence: 99%
“…In applied mathematics and analysis, previous studies by [1,14,15,16,17,18,19] have shown that the perturbation due to the presence of the conducting objects can be represented by asymptotic formulas and PT is actually the dominant term in the formula. The asymptotic formula and the corresponding PT are generally not the same for different systems.…”
Section: Introductionmentioning
confidence: 99%